Is it possible to run a change laboratory if the company does not recognize its demand as legitimate? - Lopes, Manoela Gomes Reis; de Gouveia Vilela, Rodolfo Andrade; de Almeida, Ildeberto Muniz [UNESP]; Zuccolotto, Silvana [UNESP]; Vezzá, Flora Maria Gomide (Springer Nature, 2019)
In recent years, there have been 12 fatal work accidents at a metropolitan passenger railway company. The Labor Prosecution Office contacted the School of Public Health to carry out a research making a deep analysis to understand the accidents and implementation of changes in this company to prevent accidents. Considering the presence of a civil accident inquiry and that the demand did not come from the company, the negotiation process for implementing the research was delayed and resulted in difficulties during the ethnographic phase. The research is still under progress. This chapter presents partial results of the application of the methodology, highlighting difficulties and strategies adopted by researchers in order to overcome difficulties. One of the strategies was the realization of workshops at the end of the ethnographic phase, aiming at presenting Cultural-Historical Activity Theory (CHAT) concepts and consolidating cooperation between researchers and participants, a crucial point for the activity development.